2011
DOI: 10.1089/vim.2010.0067
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Changes of Naïve and Effector/Memory CD8+ T Lymphocytes in Chronic Hepatitis B Virus Infection

Abstract: Persistent viruses, such as cytomegalovirus or human immunodeficiency virus, cause major perturbations of CD8+ T-lymphocyte subpopulations. To test whether chronic infection with hepatitis B virus (HBV) could also be responsible for such modifications, we analyzed the expression of CD27, CD28, CCR7, and perforin in blood CD8+ T lymphocytes. In comparison to healthy subjects and patients recovering from acute hepatitis B, chronic hepatitis B patients showed higher percentages of naïve CD8+ T lymphocytes (CD45RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These viruses affect the immune system by increasing immune activation and causing changes to T cell subset distribution (7,8,12,14,27). Our previous research (14) and that of others (5,7,9,11,27) have shown the importance of CD4…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…These viruses affect the immune system by increasing immune activation and causing changes to T cell subset distribution (7,8,12,14,27). Our previous research (14) and that of others (5,7,9,11,27) have shown the importance of CD4…”
mentioning
confidence: 90%
“…+ T CM and T EM CD8 + cell populations through the acute to chronic phase of the illness has mainly been noted (1,5,28). In addition, an overall decrease in the number of CD4 + T cells has been found among HBV and HCV mono-infected chimpanzees, together with inadequate CD8…”
Section: Figmentioning
confidence: 99%
“…The impact of innate immunity in liver damage also has been identified in several studies [10, 11]. Toll-like receptors (TLRs) describe a group of pattern recognition receptors (PRRs) playing critical roles in the host innate immune response [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic infections with blood-borne pathogens, such as HIV-1, HBV and HCV, tend to increase the development of memory homeostasis T cells (Carotenuto et al, 2011; Cao et al, 2014; Cillo et al, 2014; Baskic et al, 2017). During primary viral infections, virus-specific T cell responses are vigorous; however, once a persistent infection is established, both virus-specific CD4 + and CD8 + T cells become dysfunctional or difficult to detect ex vivo (Cao et al, 2014).…”
Section: Ccr7 Is Required For the Sufficient Migration Of Mature Dendmentioning
confidence: 99%